2021
DOI: 10.3390/molecules26154694
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils Extracted from Organic Propolis Residues: An Exploratory Analysis of Their Antibacterial and Antioxidant Properties and Volatile Profile

Abstract: The industrial processing of crude propolis generates residues. Essential oils (EOs) from propolis residues could be a potential source of natural bioactive compounds to replace antibiotics and synthetic antioxidants in pig production. In this study, we determined the antibacterial/antioxidant activity of EOs from crude organic propolis (EOP) and from propolis residues, moist residue (EOMR), and dried residue (EODR), and further elucidated their chemical composition. The EOs were extracted by hydrodistillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Antifungal activities of various extracts of propolis have been examined against several yeasts, such as Candida albicans, C. dubliniensis, C. glabrata, C. krusei, C. parapsisolis, C. tropicalis, Saccharomyces cerevisiae [13,[16][17][18]21,50,[54][55][56][57][60][61][62][63][64], as well as against molds, such as Alternaria solani, Alternaria alternata, Aspergillus niger, Aspergillus ochraceus, Botrytis cinerea, Cladosporium spp., Fusarium solani, Fusarium oxysporum, Mucor mucedo, Penicillium digitatum, Penicillium expansum, Penicillium chrysogenum, Rhizopus stolonifera, Rhodotorula mucilaginosa and Trichophyton spp. [9,19,43,64].…”
Section: Antifungal Properties Of Propolismentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal activities of various extracts of propolis have been examined against several yeasts, such as Candida albicans, C. dubliniensis, C. glabrata, C. krusei, C. parapsisolis, C. tropicalis, Saccharomyces cerevisiae [13,[16][17][18]21,50,[54][55][56][57][60][61][62][63][64], as well as against molds, such as Alternaria solani, Alternaria alternata, Aspergillus niger, Aspergillus ochraceus, Botrytis cinerea, Cladosporium spp., Fusarium solani, Fusarium oxysporum, Mucor mucedo, Penicillium digitatum, Penicillium expansum, Penicillium chrysogenum, Rhizopus stolonifera, Rhodotorula mucilaginosa and Trichophyton spp. [9,19,43,64].…”
Section: Antifungal Properties Of Propolismentioning
confidence: 99%
“…There is increasing information that not only polyphenolic compounds, but also essential oil components found in propolis exhibit antimicrobial activity [Ikeda, 2021. It was shown that essential oils from Brazilian propolis contain i.e., camphene, p-cymene, limonene, myrcene, α-pinene, β-pinene [55]. Many studies have proven that these chemical components occurring in essential oils of medicinal plants exerted antifungal activity mainly against Candida albicans [60,[77][78][79].…”
Section: Collected Data Analysismentioning
confidence: 99%
“…β-Caryophyllene and nerolidol were the predominant compounds of Argentinian green propolis [ 68 ]. α-Pinene and β-pinene were the principal compounds of different samples of the propolis from Brazil [ 18 ]. Limonene was identified as the chemical marker of Venezuelan propolis [ 68 ].…”
Section: Biologically Active Compounds Presented In Propolismentioning
confidence: 99%
“…Among the other organic components are polyphenols and essential oils [ 16 , 17 ]. Flavonoids, phenolic acids, and terpenoids are regarded as the main biologically active substances of propolis [ 14 , 15 , 18 , 19 ]. Okińczyc et al [ 19 ] supposed that the therapeutic effects of propolis are related mainly to the amount of polyphenols and volatile components.…”
Section: Introductionmentioning
confidence: 99%
“…A natural product recently studied worldwide is propolis, which has shown efficacy against different fungal strains, including Candida sp. [ 5 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. In this sense, it has been reported that propolis samples from different countries such as Poland, Iran, Cameroon, Brazil, the Czech Republic, Ireland, and Germany present both qualitative and quantitative antifungal activity differently in reference Candida strains such as C. albicans (ATCC 10231, 90028, 66396; CBS 562; NR 29450; SC 5314), Candida krusei (ATCC 6258, 90878; CBS 573), Candida parapsilosis (ATCC 22019; CBS 604), and Candida glabrata (CBS 07; DSM 11226; LMA 90-1085), Candida tropicalis (ATCC 9968; CBS 94), and Candida dubliniensis (CBS 7987), and on clinical isolates of Candida obtained from smears of the mouth and throat, as well as fluid from the peritoneal cavity, bronchopulmonary lavage, stoma, blood, urine, feces, and anus, identified as C. albicans , C. glabrata , C. krusei , C. dubliniensis , C. tropicalis , and C. parapsilosis [ 61 , 63 , 64 , 66 , 68 , 69 , 70 , 73 ].…”
Section: Introductionmentioning
confidence: 99%